OCHRONA ORTODOKSYJNEJ WIARY W USTAWODAWSTWIE JUSTYNIANA - Kursa, Sławomir (Zeszyty Prawnicze, 2016)
Protection of the Orthodox Religion in the Legislation of Justinian I Summary The protection of the Orthodox religion was one of the priorities in Justinian’s life and activities. However, his religious policy was not very different from that of previous Christian emperors. The aim of this article is to show that Justinian’s policy was more a result of tendencies in the legal protection of Orthodoxy which had already developed in the postConstantinian age, in other words Justinian only reinforced existing regulations; and likewise his legislation to eradicate heresy and apostasy was similar to earlier provisions. Justinian used legal measures for the protection of the True Faith in an immensely instrumental way. On the one hand he maintained and introduced numerous material sanctions against heretics and apostates; on the other hand he prescribed material advantages for the Orthodox Church and those in communion with her. There were also material incentives for those who returned to the Church. The article shows that Justinian’s measures followed the same line as the religious regulations introduced by previous Christian emperors, especially Theodosius II.